The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1971
DOI: 10.1149/1.2407827
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Boric Acid on the Dielectric Properties of Hydrous Alumina Films

Abstract: Aging hydrous aluminum oxide films in boric acid solutions accelerated the surface area decrease and markedly changed the dielectric properties of the films. The effect on dielectric properties could be removed by immersion in a borate-free electrolyte. The observations were accounted for by a model in which adsorbed borate anions increased the relaxation time of a MaxwellWagner process occurring within a compact inner region of the films. It was postulated that borate anions penetrated to the interior of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1972
1972
1999
1999

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 7 publications
(23 reference statements)
0
1
0
Order By: Relevance
“…8,9 In the present work, current bursts suggesting metastable pitting were also found after NaCl injection, but only at potentials Ϫ0.64 V vs. SCE or higher. 24 Another possibility is suggested by the work of Alwitt 34 who found that removal of borate ions from solution produced significant decreases in the resistance of the barrier layers of pseudoboehmite films on aluminum.…”
Section: Discussionmentioning
confidence: 99%
“…8,9 In the present work, current bursts suggesting metastable pitting were also found after NaCl injection, but only at potentials Ϫ0.64 V vs. SCE or higher. 24 Another possibility is suggested by the work of Alwitt 34 who found that removal of borate ions from solution produced significant decreases in the resistance of the barrier layers of pseudoboehmite films on aluminum.…”
Section: Discussionmentioning
confidence: 99%